Cover Picture: Oxygen Delivery as a Limiting Factor in Modelling Dicopper(II) Oxidase Reactivity (Chem. Eur. J. 29/2017). Issue 29 (6th March 2017) - Gülzow, Jana; Hörner, Gerald; Strauch, Peter; Stritt, Anika; Irran, Elisabeth; Grohmann, Andreas
Abstract : Oxidation of catechol to quinone facilitated by dicopper‐dependent oxidases is vital in plant defense. One of the most striking manifestations is the browning of sliced or injured fruit (painting by Gabriele Endres). Our modeling of enzyme action with a new set of synthetic dicopper(II) complexes revealed a massive increase in catalytic turnover if dioxygen‐saturated solutions are periodically treated with additional dioxygen. This effect of oxygen administration has heretofore gone unnoticed. Thus, kinetics modeling should also take into account the amplifying effect of mass transport from bubbles. More information can be found in the Full Paper by G. Hörner and A. Grohmann et al. onpage 7009 .